1972
DOI: 10.1042/bj1270893
|View full text |Cite
|
Sign up to set email alerts
|

Function of arginase in lactating mammary gland

Abstract: The potential for a considerable formation of ornithine exists in lactating mammary gland because of its arginase content. Late in lactation arginase reaches an activity in the gland higher than that present in any rat tissue except liver. Occurrence of the urea cycle can be excluded since two enzymes for the further reaction of ornithine in the cycle, carbamoyl phosphate synthetase I and ornithine carbamoyltransferase, are both absent from this tissue. Instead, carbamoyl phosphate synthetase II appears early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

1974
1974
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 19 publications
2
41
0
3
Order By: Relevance
“…Consequently there is a relative enrichment of proline and a relative deficiency of arginine in milk protein [57,260]. The enzymes required for the synthesis of proline from arginine (arginase, OAT and P5C reductase) are present in the mammary gland [249,261,262], and activities of these enzymes are co-ordinately induced during development of the lactating mammary gland [249,261]. The major isoenzyme of arginase in the mammary gland is type II [262,263], which is co-localized with OAT in the mitochondrion.…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
“…Consequently there is a relative enrichment of proline and a relative deficiency of arginine in milk protein [57,260]. The enzymes required for the synthesis of proline from arginine (arginase, OAT and P5C reductase) are present in the mammary gland [249,261,262], and activities of these enzymes are co-ordinately induced during development of the lactating mammary gland [249,261]. The major isoenzyme of arginase in the mammary gland is type II [262,263], which is co-localized with OAT in the mitochondrion.…”
Section: Arginase and Proline Synthesismentioning
confidence: 99%
“…Determination of the L/S ratio is by far the most widely used and accepted method to assess for fetal lung immaturity, [18,20,21]. Possible sources of enzymes found in amniotic fluid are mother's blood and placenta [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the inhibition of arginase by proline is not due to the ornithine that might have formed from the added proline but by proline itself. The arginase in mammary gland during lactation does not function as part of the urea cycle, because the cycle is incomplete (Folley and Greenbaum, 1947;Yip and Knox, 1972), and arginine can be converted to proline involving the enzymes arginase, ornithine aminotransferase and Al-pyrroline 5-carboxylate reductase (Yip and Knox, 1972). Proline formation from arginine has been reported in bacterial and animal systems (Costilow and Laycock, 1971;Peisach and Strecker, 1962;Strecker, 1965;Eliasson and Strecker, 1966;Hill and Chambers, 1967;Reddy and Campbell, 1969;Kaysen and Strecker, 1973).…”
Section: Proline Inhibitionmentioning
confidence: 99%
“…In mammary gland a major conversion of labelled arginine into proline occurs, without formation of labelled citrulline Linzell, 1966, 1967). It has also been reported that in the mammary gland, during lactation, the arginase activity does not function as part of the urea cycle (Folley and Greenbaum, 1947;Greengard, Sahib and Knox, 1970;Yip and Knox, 1972). This suggests that the urea cycle is inoperative in mammary gland and that arginine can be diverted through the reactions of arginase, ornithine aminotransferase and A1-pyrroline 5-carboxylate reductase to the synthesis of proline, and proline is the end product of the metabolic conversion of arginine.…”
mentioning
confidence: 99%